Down-Regulation of Lnc-CYP7A1-1 Rejuvenates Aged Human Mesenchymal Stem Cells to Improve Their Efficacy for Heart Repair Through SYNE1 - Jun Dong; Jun Dong; Jianwei Liu; Yueqiang Wen; Stephanie W. Tobin; Chongyu Zhang; Chongyu Zhang; Huiling Zheng; Zehan Huang; Yongtao Feng; Yongtao Feng; Dongcheng Zhang; et al. (Frontiers in Cell and Developmental Biology, 2020)
BackgroundSeveral long non-coding RNAs (lncRNAs) have been associated with cell senescence, termed senescence-associated lncRNAs (SAL-RNAs). However, the mechanisms involved for SAL-RNAs in aging are not fully elucidated. In the present study, we investigated the effects of SAL-RNAs on aged human bone marrow-derived mesenchymal stem cells (hBM-MSCs), and the possible means to counteract such effects to improve the regenerative capacity of aged hBM-MSCs.MethodsBy comparing the lncRNAs expression of hBM-MSCs derived from young and old individuals, lnc-CYP7A1-1 was identified as being significantly increased with age. Using predictive software, the expression of Spectrin Repeat Containing Nuclear Envelope Protein 1 (SYNE1), was found to be decreased with age. Next, through lentiviral constructs, we downregulated the expression of lnc-CYP7A1-1 or SYNE1 in hBM-MSCs separately. Additionally, hBM-MSCs proliferation, survival, migration, and senescence were investigated in vitro. In vivo, lnc-CYP7A1-1 downregulated aged hBM-MSCs were implanted into infarcted mouse hearts after myocardial infarction (MI), and cardiac function was measured. Through lentivirus-mediated downregulation of lnc-CYP7A1-1 in aged hBM-MSCs, we revealed that cell senescence was decreased, whereas cell proliferation, migration, and survival were increased. On the other hand, downregulation of SYNE1, the target gene of lnc-CYP7A1-1, in young hBM-MSCs increased cell senescence, yet decreased cell proliferation, migration, and survival. Downregulation of lnc-CYP7A1-1 in aged hBM-MSCs induced cell rejuvenation, yet this effect was attenuated by repression of SYNE1. In vivo, transplantation of lnc-CYP7A1-1 downregulated old hBM-MSCs improved cardiac function after MI.ConclusionDown-regulation of lnc-CYP7A1-1 rejuvenated aged hBM-MSCs and improved cardiac function when implanted into the infarcted mouse hearts, possibly through its target gene SYNE1.